Parasite biomass-related inflammation, endothelial activation, microvascular dysfunction and disease severity in vivax malaria - Grigg, Matthew J. (2015)
Plasmodium vivax can cause severe malaria, however its pathogenesis is poorly understood. In contrast to P. falciparum, circulating vivax parasitemia is low, with minimal apparent sequestration in endothelium-lined microvasculature, and pathogenesis thought unrelated to parasite biomass. However, the relationships between vivax disease-severity and total parasite biomass, endothelial autocrine activation and microvascular dysfunction are unknown. We measured circulating parasitemia and markers of total parasite biomass (plasma parasite lactate dehydrogenase [pLDH] and PvLDH) in adults with severe (n = 9) and non-severe (n = 53) vivax malaria, and examined relationships with disease-severity, endothelial activation, and microvascular function. Healthy controls and adults with non-severe and severe falciparum malaria were enrolled for comparison. Median peripheral parasitemia, PvLDH and pLDH were 2.4-fold, 3.7-fold and 6.9-fold higher in severe compared to non-severe vivax malaria (p = 0.02, p = 0.02 and p = 0.015, respectively), suggesting that, as in falciparum malaria, peripheral P. vivax parasitemia underestimates total parasite biomass, particularly in severe disease. P. vivax schizonts were under-represented in peripheral blood. Severe vivax malaria was associated with increased angiopoietin-2 and impaired microvascular reactivity. Peripheral vivax parasitemia correlated with endothelial activation (angiopoietin-2, von-Willebrand-Factor [VWF], E-selectin), whereas markers of total vivax biomass correlated only with systemic inflammation (IL-6, IL-10). Activity of the VWF-cleaving-protease, ADAMTS13, was deficient in proportion to endothelial activation, IL-6, thrombocytopenia and vivax disease-severity, and associated with impaired microvascular reactivity in severe disease. Impaired microvascular reactivity correlated with lactate in severe vivax malaria. Findings suggest that tissue accumulation of P. vivax may occur, with the hidden biomass greatest in severe disease and capable of mediating systemic inflammatory pathology. The lack of association between total parasite biomass and endothelial activation is consistent with accumulation in parts of the circulation devoid of endothelium. Endothelial activation, associated with circulating parasites, and systemic inflammation may contribute to pathology in vivax malaria, with microvascular dysfunction likely contributing to impaired tissue perfusion.